Poetics of Urban Environment - Glazychev, Vyacheslav (project baikal, 2007)
Environment is assumed as both object-space surroundings in their sensibly given components, and surroundings of a human being in particularly social sense revealed in observed signs of distribution of roles and positions. When focusing on the first interpretation we face mostly the «still life» vision of the city. Here the city is equated to a landscape, for example in English terminology the word 'townscape' has this very fixed meaning. In the traditional art history estimation the townscape is easily analyzed both as a whole and elementarily. When focusing on the second interpretation the surroundings are usually intensively broken down into their constituent parts: Gogol's Nevsky Avenue is a poetically shaped social-psychological «section» of the street, almost absolutely free of its topographic definiteness.The general bivalence of the word 'environment' will not be an obstacle here, but on the contrary we will consider this very bivalence as an essential characteristic of the subject. How to research this subject with indistinct frames and eluding shape, if ambivalence is its essence? This task was perfectly carried out by Italo Calvino, a writer, his «Invisible Cities» are the broadest typology of all conceivable urban environments, a collection of their poetic 'models'. The urban environment – a dense clot of spontaneous impressions and respective mental constructions – cannot be researched in vitro, whereas it could be in the past and it can be now successfully studied by art. This wonderful ability of art, abstractedly from live concreteness of urban environment, may be expressed just by means of free art history interpretation, which is not strictly bounded by the rule of unity of object and language, time and place.When and under which conditions does the urban environment act as an object of aesthetic experience and understanding? What metamorphoses does the aesthetic development of urban environment experience depending on the place and historical time? And finally, what is the peculiarity of the today's treatment of the urban environment? It is obvious, that if to gather all the above questions into summarizing one, it will be a question on formation and development of the urban environment as an object of art activity and aesthetic perception. This is not only a question of studying, but rather of understanding of urban environment as totally humanized natura naturata, developed within thousands of years.